Effects of dry-land vs. resisted-and assisted-sprint exercises on swimming sprint performance - Girold, S.; Maurin, D.; Dugue, B.; Chatard, J. C.; Millet, G. (The Journal of Strength and Conditioning Research, 2007)
This study was undertaken to compare the effects of dry-land strength training with a combined in-water resisted- and assisted-sprint program in swimmer athletes. Twenty-one swimmers from regional to national level participated in this study. They were randomly assigned to 3 groups: the strength (S) group that was involved in a dry-land strength training program where barbells were used, the resisted- and assisted-sprint (RAS) group that got involved in a specific water training program where elastic tubes were used to generate resistance and assistance while swimming, and the control (C) group which was involved in an aerobic cycling program. During 12 weeks, the athletes performed 6 training sessions per week on separate days. All of them combined the same aerobic dominant work for their basic training in swimming and running with their specific training. Athletes were evaluated 3 times: before the training program started, after 6 weeks of training, and at the end of the training program. The outcome values were the strength of the elbow flexors and extensors evaluated using an isokinetic dynamometer, and the speed, stroke rate, stroke length, and stroke depth observed during a 50-meter sprint. No changes were observed after 6 weeks of training. At the end of the training period, we observed significant increases in swimming velocity, and strength of elbow flexors and extensors both in the S and RAS groups. However, stroke depth decreased both in the S and RAS groups. Stroke rate increased in the RAS but not in the S group. However, no significant differences in the swimming performances between the S and RAS groups were observed. No significant changes occurred in C. Altogether, programs combining swimming with dry-land strength or with in-water resisted-and assisted-sprint exercises led to a similar gain in sprint performance and are more efficient than traditional swimming training methods alone.